Development and evaluation of a community respiratory physiotherapy service for children with severe neurodisability. Issue 1 (19th August 2015) - Wolff, Antonia; Griffin, Hayley; Flanigan, Moira; Everest, Sarah; Thomas, David; Whitehouse, William
Abstract: Children with severe disability often have difficulties with secretion clearance leading to recurrent lower respiratory tract infections and prolonged hospital admissions. A community respiratory physiotherapy service was developed for this client group, including a rapid response for acute respiratory illness, and an evaluation was undertaken, comparing admissions and bed-days in hospital for respiratory tract infections, emergency admissions to hospital for any cause, and admission costs for each child for the 12 months before to the 12 months with the service. Thirty-four children aged 1 to 19 years (median 5) were eligible for the "before and after" evaluation at 28 months; most had severe cerebral palsy 22 (65%), and there were also eight (23%) children with neurodegenerative and four (12%) with neuromuscular conditions. Admissions for respiratory tract infection fell from 43 to 25 (p<0.05), respiratory admission bed-days fell from 383 to 236 (p<0.01), total non-elective admissions fell from 64 to 40 (p<0.01), with admission cost savings of GBP 78, 155 (52%) per annum. This small study suggests that a community respiratory physiotherapy service can reduce hospital admissions and bed days for disabled children. The admissions cost savings have enabled the service to "pay for itself".